Resilience and prosociality: pathways to strengthen teachers' self-efficacy in the classroom - Mieres-Chacaltana, Manuel; Salvo-Garrido, Sonia; Dominguez-Lara, Sergio (Frontiers in Psychology, 2025)
This study investigates the relationship between resilience and teacher self-efficacy in Chilean elementary school teachers, considering the mediating role of prosocial behavior. Based on a cross-sectional design and a large national sample (N = 1,426), structural equation modeling (SEM) was used to analyze both direct and indirect associations. Results revealed that resilience significantly predicts teacher self-efficacy, both directly and indirectly through prosociality. Among the three self-efficacy dimensions, stronger associations were observed in instructional strategies and student engagement. These findings highlight the importance of strengthening socioemotional competencies—such as resilience and prosocial tendencies—in teacher training programs, as key mechanisms to improve classroom management, teaching effectiveness, and student motivation in educational contexts.